Home parenteral nutrition versus artificial hydration in malnourished patients with cancer in palliative care: a prospective, cohort survival study. Issue 1 (21st August 2020) - Cotogni, Paolo; Ossola, Marta; Passera, Roberto; Monge, Taira; Fadda, Maurizio; De Francesco, Antonella; Bozzetti, Federico
Abstract : Objective: The evidence base for home parenteral nutrition (HPN) in patients with advanced cancer is lacking. To compare the survival of malnourished patients with cancer undergoing palliative care who received HPN with a homogeneous group of patients, equally eligible for HPN, who did not receive HPN. Design: Prospective, cohort study; tertiary university hospital, home care, hospice. Methods: Patients were assessed for HPN eligibility according to the guidelines. In the eligible population, who received both HPN and chemotherapy was excluded, while who received only HPN was included in the HPN+ group and who received neither HPN nor chemotherapy but artificial hydration (AH) was included in the HPN− group. Results: 301 patients were assessed for HPN eligibility and 86 patients (28.6%) were excluded for having severe organ dysfunction or Karnofsky performance status <50. In outcome analysis, 90 patients (29.9%) were excluded for receiving both HPN and chemotherapy, while 125 (41.5%) were included, 89 in HPN+ group (29.5%) and 36 in HPN− group (12%). The survival of the two groups showed a significant difference favouring patients receiving HPN (median overall survival: 4.3 vs 1.5 months, p<0.001). The multivariate analysis of the risk factors for mortality showed that not receiving HPN accounted for the strongest one (HR 25.72, 95% CI 13·65 to 48.44). Conclusions: Comparative survival associated with the use of HPN versus AH showed significantly longer survival in malnourished patients with advanced cancer receiving HPN. These data support the guideline recommendation that HPN should be considered when malnutrition represents the overriding threat for the survival of these patients.